Dental caries in young male adults: prevalence, severity and associated factors Cárie dentária em homens jovens: prevalência, severidade e fatores associados - Marcelo Augusto Amaral; Luiza Nakama; Carlos Alberto Conrado; Tiemi Matsuo (Sociedade Brasileira de Pesquisa Odontológica, 2005)
The aim of the present study was to determine the prevalence and severity of dental caries as well as the needs for dental treatment in 18-year-old males from Maringá, PR, Brazil. The association of dental caries experience with socioeconomic variables was also tested. A cross sectional study was conducted in a random sample of 241 conscripts of the Brazilian Army. The adopted diagnosis criteria were those proposed by the World Health Organization. A socioeconomic questionnaire was utilized to determine family income and the criterion of the Brazil Economic Classification of the National Association of Research Enterprises. Associations among caries prevalence, DMF-T index, treatment needs and socioeconomic variables were evaluated by means of the Chi-Square, Mann-Whitney and Kruskal-Wallis tests. Caries prevalence was 82.6% and the mean DMF-T index was 4.6. Only a mean of 0.8 tooth per individual presented treatment needs. Significant statistical differences were found in caries prevalence and severity (DMF-T). The worst results were observed in the groups of lower income and purchasing power, indicating a need for the implementation of social policies that address these populations aiming at diminishing the existing differences in the health-disease process indicators. On the other hand, treatment needs were only associated to the Brazil Economic Classification Criterion variable (p < 0.05). O objetivo do presente estudo foi conhecer a prevalência e a severidade da cárie dentária, bem como as necessidades de tratamento odontológico de jovens de 18 anos de idade do sexo masculino em Maringá, Paraná, Brasil. A associação da experiência de cárie com variáveis socioeconômicas também foi testada. Foi realizado um estudo transversal em uma amostra aleatória de conscritos (n = 241) do Exército Brasileiro. Os critérios de diagnóstico adotados foram aqueles estabelecidos pela Organização Mundial de Saúde. Foram utilizados um questionário socioeconômico para aferir a renda familiar e o Critério de Classificação Econômica Brasil da Associação Nacional de Empresas de Pesquisa. Associações entre a prevalência de cárie, o índice CPO-D, a necessidade de tratamento e as variáveis socioeconômicas foram avaliadas por meio dos testes Qui-quadrado, Mann-Whitney e Kruskal-Wallis. A prevalência de cárie foi de 82,6% e o índice CPO-D médio foi igual a 4,6. Apenas 0,8 dente por indivíduo, em média, apresentou-se com necessidade de tratamento. Diferenças estatisticamente significativas foram encontradas na prevalência e na severidade de cárie (CPO-D), sendo os piores indicadores verificados nos grupos de baixa renda e baixo poder aquisitivo, indicando a necessidade de implantação de políticas sociais que contemplem essas populações, com o intuito de diminuir o diferencial nos indicadores do processo saúde-doença. Por outro lado, as necessidades de tratamento associaram-se somente à variável Critério de Classificação Econômica Brasil (p < 0,05).